2002
DOI: 10.1002/1521-4052(200211)33:11<667::aid-mawe667>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss elastischer Kennwerte auf die Eigenschaften von Blechformteilen

Abstract: Aktuelle Trends in der Automobilindustrie in Richtung Sicherheit, Kraftstoffeinsparung und Minderung von Abgasen führen zu einem vermehrten Einsatz von hoch‐ und höherfesten Stahlwerkstoffen im Karosseriebau. Durch die höherfesten Stähle lassen sich die verwendeten Blechdicken bei gleicher Belastung zum Teil deutlich reduzieren. Die Umformung dieser Werkstoffe stellt jedoch auch erhöhte Anforderungen an den Tiefziehprozess. Ursache hierfür ist die erhöhte Neigung zur Rückfederung der Blechteile aus diesem Werk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Examples for springback of hat profiles are shown in later sections. A less obvious aspect is the fact that the modulus of elasticity appears to be smaller during unloading from the plastic state than during the first loading , and seems to decrease further during subsequent reloadings and unloading s. This has been observed repeatedly in the literature [5][6][7][8][9], and also by the present authors. Although this phenomenon is probabl y a consequence of microplasticity, it is described most efficientl y in the simulations as a reduction of the elastic modulus.…”
Section: Introductionsupporting
confidence: 80%
“…Examples for springback of hat profiles are shown in later sections. A less obvious aspect is the fact that the modulus of elasticity appears to be smaller during unloading from the plastic state than during the first loading , and seems to decrease further during subsequent reloadings and unloading s. This has been observed repeatedly in the literature [5][6][7][8][9], and also by the present authors. Although this phenomenon is probabl y a consequence of microplasticity, it is described most efficientl y in the simulations as a reduction of the elastic modulus.…”
Section: Introductionsupporting
confidence: 80%
“…This is due to the fact that linear elastic strain depends on the initial modulus and the unloading stress. Since the modulus of elasticity is a constant magnitude, according to [1] linear elastic strain depends, on the tensile strength of the material. As the martensite content decrease, the non-linear strain rate affected the overall springback more remarkably, which is shown in figure 5 right.…”
Section: Discussionmentioning
confidence: 99%
“…A major disadvantage of these steels is the forming process, since with increasing strength, besides higher necessary forming forces, also their springback increases. [1] Cleveland and Gosh have shown in [2] that unloading after a plastic deformation is nonlinear. They demonstrated that springback after a plastic deformation of an aluminum alloy, as well as an AHSS consists of the known linear elastic and an additional non-linear elastic component.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, varying the modulus of elasticity permits the attainment of good correlations with real-life results. In addition [6] and [7] refer that there is an influence of the plastic strain on the modulus of elasticity.…”
Section: Sheet Metal 2007mentioning
confidence: 99%